Karipap Frozen Zurainah / Mohd Ezaidi Wahap - Wahap, Mohd Ezaidi (2021)
This business is a family business. The business run by five people who hold positions as owner/cooks, admin/manager, cooks 2, packers and food deliverymen. Karipap Frozen Zurainah is located at No.006 Kampung Dandulit, Rancangan Sungai Manila, Batu 12, Sandakan, Sabah. This company began operations in June 2021. This business concept is based on frozen food. Frozen food provided there is only one type of curry puff but the curry puff has many other fillings, it is not only potatoes but there are fillings such as chicken and meat. As we know, nowadays everyone is busy with work and needs food that is easy to get and eat right away, so we prepare this frozen curry because it is easy to cook and can be used in a long time. The target market is workers, older people and mini market who are around the area. From the observation, in the area there are very many people which makes the place the most strategic place for us to conduct our business. The food we provide is edible by everyone no matter from adults to children, and our food is also guaranteed halal because we only use halal-based ingredients. Nevertheless, our food and products can be eaten by everyone regardless of whether they are Indians, Chinese, Malays and others. Furthermore, we provide social sites such as Facebook and Instagram that make our food and products easy to identify and convenient to be obtained.